2011
DOI: 10.1016/j.ijid.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hepatitis C virus infection in patients with chronic kidney disease on conservative therapy

Abstract: Hepatitis C virus (HCV) infection is a never-ending public health problem. Many studies have investigated the incidence of HCV infection among dialysis patients, but there have only been a few epidemiological studies in renal conservative therapy. We studied 320 subjects with pre-dialysis chronic kidney disease living in Sicily, Italy. The incidence of HCV infection was 6.25%. In Europe, incidence ranges from 0.2% to 3.5%. It appears that the incidence of HCV infection is higher in the studied patient populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…International studies have shown variable results. In an Italian study of pre-dialysis CKD patients, incidence of hepatitis C was found to be 6.25% in 320 patients 13. In another study in Spain, hepatitis C antibody was present in 7.9% of 226 CKD patients with frequency of 13% in patients with creatinine clearance less than 30 ml/min 14.…”
Section: Discussionmentioning
confidence: 95%
“…International studies have shown variable results. In an Italian study of pre-dialysis CKD patients, incidence of hepatitis C was found to be 6.25% in 320 patients 13. In another study in Spain, hepatitis C antibody was present in 7.9% of 226 CKD patients with frequency of 13% in patients with creatinine clearance less than 30 ml/min 14.…”
Section: Discussionmentioning
confidence: 95%
“…13,14 The prevalence of HCV seropositivity increases with advanced CKD stage. 15 In addition, infection with HCV has also been reported to be significantly positively associated with proteinuria. 16 In a retrospective cohort study involving over 470,000 adult veterans, patients with HCV infection were more likely to develop ESRD than HCV-seronegative patients.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported in Table reveal a high frequency of HCV infection in patients with advanced pre‐dialysis CKD; some authors concluded that the current risk factors for HCV in patients receiving dialysis differ consistently from those identified two decades ago, at least in developed countries . The implementation of infection control procedures to prevent the spread of bloodborne pathogen agents (including HCV), the screening of blood for HCV, and the use of erythropoietin‐stimulating agents has dramatically reduced the post‐transfusion and nosocomial transmission of HCV within hemodialysis units.…”
Section: Hcv and Pre‐dialysis Ckd: Risk Factorsmentioning
confidence: 99%